Il Sistema previdenziale pubblico tra vincoli e scelte - DE SANTIS, GUSTAVO (Lectio Magistralis, 2019)
Social security systems are in crisis almost everywhere in the world, partly due to the bad management from the past, especially far back in time, and partly due to their intrinsic characteristics, which were not always well understood by those who designed them, and even less so by those who subsequently intervened to change them. However, removing the many layers that have gradually been added to the debate, it seems possible to focus on the few, truly relevant variables about the issue, to separate the political choices from the exogenous variables (the constraints), to bring out the consequences of the different possible choices in the long and short run, and thus to contribute to safeguarding one of the cornerstones the modern social state, even if it is downsized in the process. In doing so, it also seems appropriate to clarify the compromise point that is intended to be pursued between actuarial equity and redistribution, two unfortunately incompatible, but still very relevant goals, which have always (confusingly) been present in the debate on the social security systems.